Building Customer Loyalty Through Brand Image: A Case Study on Balong Aja Café in Garut - Junaedi, J.; Pramudhita, Cinta Aura (Golden Ratio of Data in Summary, 2024)
In an era of increasingly fierce business competition, building customer loyalty is one of the important factors for business continuity, especially in the culinary sector. This study aims to determine the effect of brand image on customer loyalty at Café Balong Aja, Garut. This study uses a quantitative approach with descriptive correlational research. The population in this study were Café Balong Aja customers who visited more than once, with the sampling technique using purposive sampling. The sample used amounted to 100 respondents who met the research criteria. The location of this research was at Café Balong Aja, which is located at Cilopang Adventure Camp, Garut, with the research time lasting six months, from January 2024 to June 2024. Data were obtained through questionnaires distributed to customers and analysed using SPSS. The results showed that brand image has a positive influence on customer loyalty, although the effect is fairly low. This shows that although brand image can increase customer loyalty, other factors such as product quality, service, and customer experience also play an important role. The implication of this study is that it is important for culinary entrepreneurs to strengthen brand image while improving product quality and service to build higher customer loyalty.